2007
DOI: 10.1089/cap.2006.0039
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic-Related Abnormal Involuntary Movements and Metabolic and Endocrine Side Effects in Children and Adolescents

Abstract: There has been a remarkable increase in prescription rates of antipsychotics in children and adolescents in recent years. Their side effects are a neglected area of research in this population, despite its vulnerability. In this cross-sectional study, we compared the presence of side effects in 60 children and adolescents who had taken antipsychotic medication for less than 1 month and 66 who had been receiving treatment with antipsychotics for more than 12 months. Mean age for the total sample was 15.62 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 35 publications
(28 reference statements)
4
45
0
2
Order By: Relevance
“…This may indicate a higher susceptibility to extrapyramidal symptoms with olanzapine as compared to quetiapine in this population. In a previous study on SGA tolerability in a pediatric population, we reported that patients treated mostly with SGAs over a one-year showed more dyskinetic movements than patients treated for less than 1 month [22]. Maturation of the dopamine system during childhood and adolescence may affect susceptibility to motor side effects differently, depending on age.…”
Section: Discussionmentioning
confidence: 92%
“…This may indicate a higher susceptibility to extrapyramidal symptoms with olanzapine as compared to quetiapine in this population. In a previous study on SGA tolerability in a pediatric population, we reported that patients treated mostly with SGAs over a one-year showed more dyskinetic movements than patients treated for less than 1 month [22]. Maturation of the dopamine system during childhood and adolescence may affect susceptibility to motor side effects differently, depending on age.…”
Section: Discussionmentioning
confidence: 92%
“…[11][12][13]. Best practice guidelines were considered as being met if the clinician indicated that he or she was performing a regular laboratory evaluation or was aware that another physician was performing it.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Another source of concern pertains to the adverse effects of antipsychotic medications, some of which may be more common in youth compared with adults. These adverse effects include movement disorders, 12 metabolic problems, weight gain, 13 and sedation.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Weight increase in children raises the concern that, if treated for long periods, these patients are at higher risk of insulin resistance, diabetes, hypertension or cardiovascular disease in the future. If drugs likely to induce weight gain have to be used, compensatory behavioral or pharmacological approaches should be implemented (Correll 2007;Laita et al 2007). …”
Section: Antipsychotics In Child Psychotic Episodes 333mentioning
confidence: 99%